A Tongan Tapua in the Pitt Rivers Museum: Historiographical Notes and Curatorial Reflections - Coote, Jeremy (Waka Kuaka, 2015)
In a recent account, in the Journal of the Polynesian Society, of Tongan tapuaâ€”â€œpolished ivory shrinesâ€â€”Fergus Clunie refers to an example in the University of Oxfordâ€™s Pitt Rivers Museum as being â€œtenuously provenancedâ€ to Cookâ€™s voyages. A detailed discussion of the tapuaâ€™s documentation is provided to demonstrate how this â€œtenuousâ€ provenance has no basis in fact, before other possible histories are considered.